Designing of Medical processor unit for Intelligent network-based Medical usage - P. ILA Chandana Kumari; P. Gayathri; N. Rajesh; Syed Umar; G. Chandra Sekhar; Azeem Mohammed Abdul (Institute of Advanced Engineering and Science, 2016)
This medical design conventions of books and deductive method (MPU). the development of research and the success of many already, we have found the cause of architecture MPU. On the unique features of the processor in question it is coded in different areas of medicine (MOPC). working from a very close bilateral processor MPU. Each issue has a special feature code for the hardware supply chain on the steps and produce a special version of the code and the victim (s). Illness, Doctor MOPC mph dismounted and made a series of sub-processes, and to launch the second law of medical devices. If the computer system of a victim and has a specific digital for logic, and victims of medical devices that operate in the blood, tissues, operating theaters, medical staff, medical costs and variables, etc. We follow the process that the patient design of medical networks and overlapping and development computer.